Analysis of free-living daytime movement in patients with migraine with access to acute treatment - Jonas Van Der Donckt; Nicolas Vandenbussche; Mathias De Brouwer; Bram Steenwinckel; Marija Stojchevska; Femke Ongenae; Koen Paemeleire; Sofie Van Hoecke (The Journal of Headache and Pain)
Abstract Background Motion can exacerbate headache during a migraine attack, potentially leading to avoidance of routine physical activity. Advances in wrist-worn actigraphy facilitate objectively analyzing how headache episodes affect physical activity in everyday settings. The primary hypothesis was hypoactivity during daytime headache events. Secondary hypotheses are hypoactivity during the prodromal and postdromal hours closest to the headache event. Methods During a 90-day prospective observational study, participants diagnosed with migraine wore an actigraphy device on their non-dominant wrist during daily life and work, while also logging migraine-related data in a dedicated smartphone application. There were no restrictions on use of acute and preventive headache treatments. Data from the wrist-worn accelerometer were used to (i) calculate activity energy expenditure, and (ii) predict types of human activities. These metrics were used to compare daytime prodromal, ictal, and postdromal phases of headache events with time-matched intervals during non-headache periods. Results A significant reduction in daytime physical activity was observed during the ictal phase of headache attacks, as evidenced by decreases in both activity energy expenditure and human activity recognition prediction metrics. A reduction in movement was also observed during evening hours (18:00–24:00) on headache days. However, no significant physical activity changes were noted in the prodromal and postdromal phases. Reduced physical activity was more pronounced during the ictal phase when acute treatments were ineffective. Conclusions This study is the first to examine the impact of headache on physical activity levels during daytime headache events by assessing changes in daily activities and activity energy expenditure in individuals with migraine, within their habitual environments and without restrictions on acute medication use. Our findings confirm reduced movement during the ictal phase of migraine attacks, supporting the primary hypothesis. Wrist-worn actigraphy further indicated that this reduction is more pronounced when patients experience movement sensitivity. Evening hypoactivity is also observed on headache days. Furthermore, attacks with ineffective acute treatment or moderate-to-high intensity were associated with more pronounced reductions in movement. In contrast, our data did not support the secondary hypothesis that physical activity would decrease during daytime prodromal and postdromal periods. Trial registration NCT04983186 ( www.ClinicalTrials.gov ). Graphical Abstract